2018
DOI: 10.1007/s00520-018-4107-3
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual well-being associated with personality traits and quality of life in family caregivers of cancer patients

Abstract: This study points out that caregivers who experience low SWB have a poorer QoL and more problematic intrapsychic aspects of personality, such as low self-acceptance of their own emotions, are self-refusing and unable to be in contact with their own feelings. This suggests that spirituality could be a source of strength and a potential avenue for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…Regarding the year of publication, 36 out of 62 articles were published in 2017 and 28 in 2018. Countries where the respective studies were conducted were the USA/Canada ( n = 23) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31], Scandinavia ( n = 7) [32,33,34,35,36,37,38], UK ( n = 4) [39,40,41,42], Germany ( n = 4) [43,44,45,46], Southern Europe (Italy, Portugal, Spain; n = 8) [47,48,49,50,51,52,53,54], East Asia (Japan, China, Korea, Taiwan; n = 4) [55,56,57,58,59,60], Australia/New Zealand ( n = 4) [61,62,63,64], other ( n = 4) [65,66,67,68], and multinational ( n = 2) [69,70].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the year of publication, 36 out of 62 articles were published in 2017 and 28 in 2018. Countries where the respective studies were conducted were the USA/Canada ( n = 23) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31], Scandinavia ( n = 7) [32,33,34,35,36,37,38], UK ( n = 4) [39,40,41,42], Germany ( n = 4) [43,44,45,46], Southern Europe (Italy, Portugal, Spain; n = 8) [47,48,49,50,51,52,53,54], East Asia (Japan, China, Korea, Taiwan; n = 4) [55,56,57,58,59,60], Australia/New Zealand ( n = 4) [61,62,63,64], other ( n = 4) [65,66,67,68], and multinational ( n = 2) [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven studies reported on relatives of advanced cancer patient’s [9,10,11,13,15,16,17,18,19,20,21,22,23,24,26,27,28,29,30,31,32,34,36,37,38,39,42,43,44,46,47,48,49,50,51,52,53,55,56,57,58,59,60,61,65,66,67] and 15 studies included relatives of mixed patient samples [12,14,25,33,35,40,41,45,54,62,63,64,68,69,70]. The environment in which the patient received palliative or hospice care were home care in 18 studies [10,14,25,26,27,30,3...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Family members caring for loved ones with chronic disease such as cancer are at high risk for psychological distress, which may impair their quality of life due to elevated burden. Previous studies point out that caregivers who experience low spiritual well-being have a poorer Quality of Life and more problematic intrapsychic aspects of personality, such as low acceptance of their own emotions and failure to be in contact with their own feelings [39,40]. It is important to identify the problems and address the spiritual needs of caregivers in order to provide support for their spiritual well-being and reduce their suffering.…”
Section: Discussionmentioning
confidence: 99%